(E)‐2‐methoxy‐4‐(3‐(4‐methoxyphenyl)prop‐1‐en‐1‐yl)phenol suppresses ovarian cancer cell growth via inhibition of ERK and STAT3. Issue 9 (30th March 2017) - Zheng, Jie; Son, Dong Ju; Lee, Hye Lim; Lee, Hee Pom; Kim, Tae Hoon; Joo, Jung Heun; Ham, Young Wan; Kim, Wun Jae; Jung, Jae Kyung; Han, Sang‐Bae; Hong, Jin Tae
Abstract : In the present study, we synthesized several non‐aldehyde analogues of (E)‐2, 4‐bis(p‐hydroxyphenyl)‐2‐butenal which showed anti‐cancer effect. Interestingly, among the 16 compounds, we found that (E)‐2‐methoxy‐4‐(3‐(4‐methoxyphenyl)prop‐1‐en‐1‐yl)phenol (MMPP) showed the most significant anti‐proliferative effect on PA‐1 and SK‐OV‐3 ovarian epithelial cancer cells. MMPP treatment (0‐15 µg/mL) induced apoptotic cell death, enhanced the expression of cleaved caspase‐3, and cleaved caspase‐9 in a concentration dependent manner. Notably, DNA binding activity of STAT3, phosphorylation of extracellular signal‐regulated kinase (ERK) and p38 was significantly decreased by MMPP treatment. However, ERK siRNA augmented MMPP‐induced inhibitory effect on cell growth rather than p38 siRNA or JNK siRNA. Moreover, combination treatment of MMPP with ERK inhibitor U0126 (10 µM) augmented MMPP‐induced inhibitory effect on cell growth and DNA binding activity of STAT3, and enhanced expression of cleaved caspase‐3 and cleaved caspase‐9. In addition, STAT3 siRNA transfection augmented MMPP‐induced cell growth inhibition. In PA‐1 bearing xenograft mice model, MMPP (5 mg/kg) suppressed tumor growth significantly. Immunohistochemistry staining showed that the expression levels of p‐ERK, PCNA, p‐STAT3 were decreased while the expression level of caspase‐3 was increased by MMPP treatment. Thus, MMPP may be a promising anti‐cancer agent in ovarian epithelial cancer treatment.